Alih Fungsi Lahan Dari Sawah Ke Non Sawah Pada Masyarakat Pedesaan Sumber Makmur, Kecamatan Sungai Rumbai,Mukomuko, Provinsi Bengkulu - Irwan, Irwan; Fasihun, Nur; Sianturi, Juliana (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2023)
This research is motivated by the conversion of land from rice fields to non-rice fields that occurs in rural communities. The purpose of this study is to analyze the causes and impacts of land conversion from rice fields to non-rice fields in rural communities. This study uses a qualitative approach with a descriptive type. This research was conducted in Sumber Makmur Village, Sungai Rumbai District, Mukomuko Regency, Bengkulu Province. Data collection methods were carried out in several ways, namely: non-participant observation, in-depth interviews, and document data collection. The withdrawal of informants was carried out by purposive sampling technique and the informants in this study were rice farmers who experienced changes in their livelihoods from rice fields to non-rice fields. The unit of analysis of this research is individuals who experience changes in their livelihoods and data analysis using the Miles and Huberman model with several stages, namely data collection, data reduction, data presentation, and conclusion drawing. The results showed that from 1,500 residents in Sumber Makmur 90% changed the function of land from rice fields to non-rice fields. The cause is the first land function: rice has failed to harvest, the second is the increasing need for life, the yield of rice that is obtained is uncertain. As a result, the change of land function from rice fields to non-rice fields or land conversion has an impact on natural disasters, job losses and production decreases.